THE APPLICATION OF CONTENT AND LANGUAGE INTEGRATED LEARNING APPROACH IN IMPROVING STUDENTS’ ENGLISH SPEAKING ABILITY AT MTsN 2 KUNINGAN WEST JAVA - Dadang Solihat; Fahrus Zaman Fadhly; Cucu Suhartini (Indonesian Journal of Learning and Instruction, 2024)
This Classroom Action Research aims at assessing the effectiveness of applying the Content and Language Integrated Learning (CLIL) Approach to enhance the English speaking skills of 7th-grade students at MTsN 2 Kuningan, West Java. The research is conducted in iterative cycles involving planning, action, development, and reflection by Mertler. The study involves 32 students in 12 sessions within one semester 17 July to 13 November 2023. The primary focus is on integrating learning materials with English teaching to elevate students' speaking proficiency. Throughout the research, student progress is meticulously monitored and assessed in each cycle, utilizing speaking ability tests, classroom observations, and reflections from both teachers and students. Qualitative data is obtained from interviews and observations which are then analyzed using descriptive qualitative. Meanwhile, quantitative data were obtained from the results of the pre-cycle test, cycle one test, cycle two test and cycle three test which were then analyzed using simple statistics. The outcomes reveal a noteworthy improvement in the English speaking abilities of grade 7 students following the implementation of CLIL. The results showed an increase from cycle one to three. In cycle one student speaking skills reached 16 students or 50% of them got complete scores. In cycle two as many as 26 students (75%) achieved complete scores, and in cycle three as many as 31 (96%) students completed it succesfully. This approach not only enhances language proficiency but also fosters heightened engagement and increased enthusiasm for learning English. These positive findings substantiate the efficacy of the CLIL Approach in advancing the English speaking skills of 7th-grade students at MTsN 2 Kuningan, West Java. Additionally, these results serve as a foundation for the development of more effective learning strategies in the future.